Common features of polyomavirus mutants selected on PCC4 embryonal carcinoma cells. - Melin, F (1985)
The genomic rearrangements of six polyomavirus mutants selected on PCC4 embryonal carcinoma cells have been compared and their common characteristics pointed out. All mutants show a duplication which includes at least the adenovirus type 5 (Ad5) E1A-like enhancer core sequence plus a deletion of variable size and location. The presence of the second enhancer core sequence, the SV40-like enhancer, is not required for expression of the PyEC PCC4 phenotype. Two of these mutants are also able to express polyomavirus T antigen on F9 and LT1 cells. Multiadaptation seems to require the duplication of the Ad5 E1A-like core sequence, the maintenance of the SV40-like core sequence and a local change in DNA stability.